2009
DOI: 10.1016/j.mad.2009.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and anti-inflammatory vasoprotective effects of caloric restriction in aging: Role of circulating factors and SIRT1

Abstract: Endothelial-dysfunction, oxidative stress and inflammation are associated with vascular aging and promote the development of cardiovascular-disease. Caloric restriction (CR) mitigates conditions associated with aging, but its effects on vascular dysfunction during aging remain poorly defined. To determine whether CR exerts vasoprotective effects in aging, aortas of ad libitum (AL) fed young and aged and CR-aged F344 rats were compared. Aging in AL-rats was associated with impaired acetylcholine-induced relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
241
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(250 citation statements)
references
References 45 publications
8
241
1
Order By: Relevance
“…Although we cannot compare absolute differences in the amount of superoxide production between arteries due (Miller et al 2005(Miller et al , 2009. Similar to previous studies, we find that scavenging superoxide improves EDD in conduit and cerebral arteries from old mice (Blackwell et al 2004;Lesniewski et al 2009;Mayhan et al 2008;Modrick et al 2009) and does not affect EDD in conduit arteries from young or old CR mice (Csiszar et al 2009). However, we demonstrate that scavenging superoxide in the MCA from young and old CR mice results in reduced EDD, which is in accordance with previous studies demonstrating reactive oxygen species contribute to the dilation of resistance arteries in skeletal muscle (Sindler et al 2013;Trott et al 2011), cardiac muscle (Miura et al 2003;Feng et al 2010;Kang et al 2011), and cerebral tissue (Drouin et al 2007).…”
Section: Oxidative Stresssupporting
confidence: 81%
See 3 more Smart Citations
“…Although we cannot compare absolute differences in the amount of superoxide production between arteries due (Miller et al 2005(Miller et al , 2009. Similar to previous studies, we find that scavenging superoxide improves EDD in conduit and cerebral arteries from old mice (Blackwell et al 2004;Lesniewski et al 2009;Mayhan et al 2008;Modrick et al 2009) and does not affect EDD in conduit arteries from young or old CR mice (Csiszar et al 2009). However, we demonstrate that scavenging superoxide in the MCA from young and old CR mice results in reduced EDD, which is in accordance with previous studies demonstrating reactive oxygen species contribute to the dilation of resistance arteries in skeletal muscle (Sindler et al 2013;Trott et al 2011), cardiac muscle (Miura et al 2003;Feng et al 2010;Kang et al 2011), and cerebral tissue (Drouin et al 2007).…”
Section: Oxidative Stresssupporting
confidence: 81%
“…Lifelong CR completely prevented this age-related decline in EDD in conduit arteries (carotid), but only partially prevents the decline in cerebral resistance arteries (MCA). As previous studies have only focused on the effect of lifelong CR on conduit artery function (Csiszar et al 2009) …”
Section: Endothelium-dependent Dilationmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that arterial SIRT1 activity is reduced with aging and contributes to the age‐related impairment in endothelial function (Donato et al ., 2011; Gano et al ., 2014). We and others also have shown that lifelong CR prevents (Csiszar et al ., 2009; Donato et al ., 2013) and short‐term CR reverses (Rippe et al ., 2010) the age‐associated decline in endothelial function and that these effects are associated with enhanced arterial SIRT1 activity. Consistent with these observations, we recently found that 4 weeks of treatment with the SIRT1 activator SRT1720 restores endothelial function (i.e., EDD) in old mice (Gano et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%